Spirals of science - Pavlenko, Anatolii (Advances in Social Sciences Research Journal, 2019)
One of the reasons for writing this paper was the understanding that it is necessary to once again show the complex effect of electromagnetic radiation on living organisms: the electromagnetic fields themselves and the torsion components of these fields. Karl von Reichenbach also studied some radiation, which was called “Odo”, other researchers called this radiation in their own way.It is hard to believe that the nature is so generous and comprises so many undiscovered forces and fields. Most probably researchers have dealt with various aspects of the same phenomena during their investigations. Reality is like this. In our opinion, the most appropriate notion of these fields should reflect their physical nature and then to be called “torsion fields” although western researchers call them longitudinal electromagnetic waves, tachyon or Tesla radiant energy etc. The recent theoretical advance has significantly changed the approach to the problem of protecting people and animals from the negative impact of telecommunication systems on them.